Impact of Halal Awareness On Intention Toward Halal Tourism: A Study On Generation Z Muslims In Bengkulu - Romadon, Taufik; Hendri, Hendri; Parwito, Parwito (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: Identify the key factors influencing the travel intentions of Generation Z Muslims in Bengkulu to visit halal tourism destinations, using the Theory of Planned Behavior (TPB) model approach. The study targeted Generation Z Muslims residing in Bengkulu Province, with respondents selected through purposive sampling. Results: Indicate that the intention to visit halal tourist destinations is significantly influenced by factors such as attitudes, perceived behavioral control, subjective norms, and halal awareness. All of these independent factors were found to have a positive effect on travel intentions. Findings: Provide valuable insights for stakeholders in the tourism industry, especially in developing halal tourism products and services that cater to the specific preferences and needs of Generation Z Muslims. Originality : While TPB has been used in past studies, applying it to the context of halal tourism for Generation Z Muslims in Bengkulu is unique. The emphasis on halal awareness as a key influencing factor adds an innovative layer to the existing framework. These results can contribute to enhancing the marketing strategies of halal tourism destinations, ensuring their appeal to this demographic group. Conclussions: Attitude, perceived behavioral control, subjective norms, and halal awareness all significantly influence the intention of Generation Z Muslims to visit halal tourism destinations. Type of Paper : Empirical Research Article